Home Health Agencies With More Socially Vulnerable Patients Have Poorer Experience of Care Ratings. (March 2022) - Wang, Jinjiao; Ying, Meiling; Li, Yue
Objectives: Examine the relationships between dual eligibility and race/ethnicity characteristics of Medicare-Certified Home Health Agencies (CHHAs) and experience of care ratings. Methods: Analysis of 2017 national Consumer Assessment of Healthcare Providers and Systems and matched datasets of 10, 906 CHHAs Results: CHHAs with higher concentrations of dual-eligible patients were less likely to have high experience of care ratings for all three domains (e.g., for care delivery, quartile 4 vs. 1: odds ratio [OR] = 0.622, p < .001); CHHAs with higher concentrations of racial/ethnic minorities generally were less likely to have high experience of care ratings in care delivery (e.g., Black: quartile 4 vs. 1: OR = 0.418, p <0.001), communication (e.g., Black: quartile 4 vs. 1: OR = 0.316, p <0.001), and specific care issues (e.g., Hispanic: quartile 4 vs. 1: OR = 0.397, p < .001). Discussion: CHHAs with greater concentrations of dual-eligible patients and racial/ethnic minorities were more likely to have poor experience of care ratings.